Polydatin ameliorates lipid and glucose metabolism in type 2 diabetes mellitus by downregulating proprotein convertase subtilisin/kexin type 9 (PCSK9). Issue 1 (December 2016) - Wang, Yu; Ye, Jiantao; Li, Jie; Chen, Cheng; Huang, Junying; Liu, Peiqing; Huang, Heqing
Abstract Background Abnormalities in lipid and glucose metabolism are constantly observed in type 2 diabetes. However, these abnormalities can be ameliorated by polydatin. Considering the important role of proprotein convertase subtilisin/kexin type 9 (PCSK9) in metabolic diseases, we explore the possible mechanism of polydatin on lipid and glucose metabolism through its effects on PCSK9. Methods An insulin-resistant HepG2 cell model induced by palmitic acid (PA) and a db/db mice model were used to clarify the role of polydatin on lipid and glucose metabolism. Results In insulin-resistant HepG2 cells, polydatin upregulated the protein levels of LDLR and GCK but repressed PCSK9 protein expression, besides, polydatin also inhibited the combination between PCSK9 and LDLR. Knockdown and overexpression experiments indicated that polydatin regulated LDLR and GCK expressions through PCSK9. In the db/db mice model, we found that polydatin markedly enhanced GCK and LDLR protein levels, and inhibited PCSK9 expression in the liver. Molecular docking assay was further performed to analyze the possible binding mode between polydatin and the PCSK9 crystal structure (PDB code: 2p4e), which indicated that steady hydrogen bonds formed between polydatin and PCSK9. Conclusions Our study indicates that polydatin ameliorates lipid and glucose metabolism in type 2 diabetes mellitus by downregulating PCSK9.